PENINGKATAN KEMAMPUAN BERKOMUNIKASI DENGAN MEDIA PAPIN (PAPAN PINTAR) PADA SISWA KELAS V - Kamala Asrih Sastri; Joni Bungai; Carolina Fransiska (PGSD FKIP UPR, 2025)
This research is based on the low communication skills of students in Indonesian learning, especially in the material